Change in retinal layer thickness and vascular parameters in preclinical Alzheimer's disease: A 2‐year longitudinal study: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Bruinenberg, Annelies E.; van de Kreeke, Aleid; Verbraak, Frank; Bouwman, Femke H.; Yaqub, Maqsood; Van Berckel, Bart N.M.; Tomassen, Jori; den Braber, Anouk; Visser, Pieter Jelle
Abstract: Background: The past year, the retina has received increasing attention as a possible biomarker for (preclinical) Alzheimer's disease (AD). Though cross‐sectional differences where inconsistently replicated in literature, longitudinal change over time of retinal layer thickness and/or retinal vascular parameters (RVPs) may differ between preclinical AD and controls. Method: 149 cognitively healthy monozygotic twins aged ≥60 were included from the EMIF‐AD PreclinAD study. 1 Participants were classified as preclinical AD (Aβ+) based on a positive [18F]flutemetamol PET image and as controls (Aβ‐) on a negative flutemetamol PET image. As a continuous measure of Aβ aggregation we used the [18F]flutemetamol PET binding potential ( BP ND ). At baseline and follow‐up, after a mean of 22 months (range 15 – 32 months), the total and individual inner retinal layer thickness in the macular region (ETDRS ring), the peripapillary retinal nerve fiber layer thickness and 7 RVPs were measured on optical coherence tomography (OCT) and fundus images. OCT measurements could be analyzed in 145 participants and fundus images in 114 participants. Ocular measurements were compared between Aβ+ and Aβ‐ participants and related to the BP ND . Result: There were no differences in change over time in any of the measured retinal layer thicknesses between pre‐clinical AD patients (n=16) and controls (n=129) (see figure 1). We did, however, find a positive association between BP ND values and an increase in the inner plexiform layer (IPL) thickness in the inner perifoveal ETDRS ring (CI: 0.575 – 2.841, p=0.003). Although arteriolar caliber, venular caliber and tortuosity of arteries all showed a significant decrease over time in the total group, no differences were found between Aβ+ (n=13) en Aβ‐ participants (n=111, table 1), nor did these RVP changes show a relation to BP ND value at baseline. Conclusion: The use of OCT measurements and RVPs as a longitudinal screening method for preclinical AD seems limited, but IPL changes may serve as a starting point for future research. Reference: (1) Konijnenberg E, Carter SF, Ten Kate M, den Braber A, Tomassen J, Amadi C, et al. The EMIF‐AD PreclinAD study: study design and baseline cohort overview. Alzheimers Res Ther. 2018;10(1):75.